Causes and Countermeasures of Business Administration Teaching in Colleges and Universities - MA, Tiaoxiao; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
The subject of business administration has become a multi-field intersecting theory, strategy and technology, which is widely used. The purpose of running a business administration major in colleges and universities is to export professional talents with rich theoretical knowledge, strong practical ability and strong post adaptability to the society. This paper mainly analyzes the characteristics of business administration teaching in colleges and universities and the reasons for the existence of the teaching process. And put forward targeted corrective measures.